DETERMINATION OF THE RELATIVE SPEED FOR SCREENING BULK MATERIALS - Fedoriv, Viktor; Stechyshyn, Myroslav; Martynyuk, Andrii; Kurskoi, Volodymyr; Рereima Andrii (SWorld-Ger Conference proceedings, 2024)
The article deals with the problems of the influence of the limit velocity on the process of sieving bulk materials; parabolic fall of a product particle through the sieve cells, as well as the passage of a particle through a hole equal to its diameter; p